Life Challenges of life, reptiles and amphibians, mammals. (DVD). - Attenborough, David (California BBC Worldwide Ltd. Program, 2010)
Challenges of life : In nature, living long enough to breed is a monumental struggle. Many animals and plants go to extremes to give themselves a chance. Uniquely, three brother cheetahs band together to bring down a huge ostrich. Aerial photography reveals how bottlenosed dolphins trap fish in a ring of mud, and time-lapse camerasw show how the Venus flytrap ensnares insect victims. The strwberry frog carries a tadpole high into a tree and drops it in a water-filled bromeliad. The frog must climb bacj from the ground everyday to feed it. Fledging chinstrap penguins undertake a heroic and tragic journey through the broken ice to get out to sea. Many can barely swim.
Reptile and Amphibians : Reptiles and amphibians look like hang-overs from the past. But they overcome their shortcomings through amazing innovation. The pebble load turns into a rubber ball to roll and bounce from its enemies. Extreme slow-motion shows how a Jesus Christ lizard runs on water, and how a chameleon fires an extendable tongue at its prey with unfailing accuracy. The camera dives with a Niuean sea snake, which must breed on land but avoids predators by swimming to an air bubble at the end of an underwater tunnel. In a TV first, Komodo dragons hunt a huge water-buffalo, biting it to inject venom, then waiting for weeks until it dies. Ten dragons strip the carcass to the bone in four hours. (Taken from the case)
Mammals: Mammals dominate the planet. They do it through having warm blood and by the care they lavish on their young. Weeks of filming in the bitter Antartic winter reveal how a mother Weddell seal wears her teeth down keeping open a hole in the ice so she can catch fish for her pup. A powered hot air balloon produces stunning images of millions of migrating bats as they converge on fruiting trees in Zambia, and how-motion cameras reveal how a mother rufous sengi exhaust a chasing lizard. A gyroscopically stabilised camera moves alongside migrating caribou, and a diving team swim among the planet's biggest fight as male humpback whales battle for a female. (Taken from the case)
From the award-winning BBC Natural History Unit, makers of Planet Earth and the Blue Planet: Seas of Life, this is the original UK broadcast version of Life, with narration by renowned naturalist David Attenborough and music by Oscar and Emmy winning composer George Fenton
A BBC / Discovery Channel / SKAI / Open University Co-Production
Keywords: Life; Reptiles; Amphibians; Mammals